THE SEA SURFACE TEMPERATURE AT THE EASTERN PACIFIC OCEAN IN THE SOUTHERN HEMISPHERE FROM THE IMAGES OF THE AVHRR / 2 SENSOR OF THE NOAA-14 POLAR ORBIT SATELLITE - Rojas Acuña, Joel (2001)
The objective of this work is the estimation of the temperature of the sea surface in the Eastern Pacific Ocean of the Southern Hemisphere from the images of the meteorological satellite of polar orbit NOAA-14 (National Administration of Atmospheric Oceanography). The study area ranges from the Peruvian coast, 70 ° W to 90 ° W of geographic longitude and from 2 ° S to 22 ° S of geographic latitude. This parameter will be applied in the determination of thermal fronts or fishing fronts. The original HRPT (High Resolution Picture Transmition) format image data is from January 1999. During the initial processing of the image data, the original HRPT format (16 bits) has been converted into another BURL format (Bradford University Research Limited) (10 bits) of interest to us. The threshold technique has been used on channels 1 and 5 for the removal of clouds. The size of the original images is 2048 x 2048 pixels. The sea surface temperature is in degrees Celsius and the arithmetic mean method has been used to obtain an average image. This monthly average is only 10 days of the month of January 1999. A color palette is applied to differentiate the values ​​of the temperature of the sea surface that has an spatial resolution of 2 km and is in intervals of 1 ° C from 17 ° C to 33 ° C. The temperature of the sea surface near the Peruvian coast is of lower magnitude than in the most remote part. In these product images many clouds have been observed over the sea and over land. A monthly average based on only 10 images clearly shows the El Niño current in northern Peru. A validation of the estimated data with those measured in situ is pending by some institutions that carry out studies using the same parameter.